Designing a Structural Model of Human Resource Management Practices Focused on the Elderly in Public Organizations - Mohammad Ali Fadaei; Hossein Mansoori; Tayebeh Abbasnejad (بهداشت و ایمنی کار, 2025)
Introduction: Demographic changes are an inevitable phenomenon in today’s organizations. By acknowledging the aging of the workforce as a significant organizational challenge, the purpose of this research is to design a structural model of elderly-oriented human resource management measures in public organizations. Material and Methods: This study is categorized as applied in terms of objective, descriptive-survey in terms of approach, and a mixed-method design (qualitative-quantitative) in terms of data collection. The information gathering tools used to review the research literature were library research methods, while a questionnaire was employed for collecting field data. Initially, the Delphi method was utilized to extract and identify elderly-oriented human resource management practices. In the second phase, a quantitative method was used to validate the model of elderly-oriented practices in public organizations and assess the current status of these practices. Results: The results obtained from the model’s goodness-of-fit in SmartPls 3 software and confirmatory factor analysis indicated high validity of the elderly-oriented human resource management practice model. Conclusion: Additionally, the findings revealed that, from the perspective of the study’s employees, the status of elderly-oriented human resource management practices in terms of implementation was not in a desirable state and did not meet employees’ expectations.